Effect of Annealing Time on Structural and Magnetic Properties of Fe68Pd32 Nanoparticles Synthesized by Sonoelectrodeposition - Nam, Nguyen Hoang; Hoi, Nguyen Tien; Trung, Truong Thanh; Hong, Tran Thi; Quynh, Luu Manh; Luong, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics, 2022)
Fe 68 Pd 32 nanoparticles were prepared by sonoelectrodeposition with subsequent annealing at 600 o C for a series of times from 1 h to 6 h. The annealing transformed disordered face-centered cubic (fcc) phase in the as-prepared samples into a multi-phase material containing an ordered L1 0 FePd, fcc FePd and body-centered cubic (bcc) Fe phases. After annealing at 600°C for 6 h the hard magnetic phase L1 0 -FePd and soft magnetic fcc-FePd phase coexist. The structural and magnetic properties of the samples were studied in dependence of annealing time. The decrease of coercivity with increasing annealing time from 1 h to 4 h is suggested to occur by formation of multi-L1 0 domain particles, while the increase of coercivity with increasing annealing time from 4 h to 6 h is proposed due to the multiphase nature of the nanoparticles samples.